Study of Nutrient Foramen in Humerus - Sintakala, Chandan; Manandhar, Prabina (Journal of College of Medical Sciences-Nepal, 2020)
Background Nutrient foramen is the gateway for the nutrient artery to provide nutrition in different parts of the bone which play important role in healing during fracture, trauma and also important for bone grafting. The aim the study is to identify the number of nutrient foramen in dry humerus and to observe direction as well as allocation of the nutrient foramen in surfaces and borders. Methods The sample for the study were collected from medical and dental colleges of Nepal in years ranging from 2018 to 2020 AD and the height were measured by the help of using vernier caliper, probe was introduced in nutrient foramen to confirmed its direction. The numbers of nutrient foramen were noted in copy and analyzed the statistics by using software called the SPSS (Statistical Package for the Social Sciences) 20. Results In the study of 200 sample of humerus from the department of anatomy from different medical and dental college of Nepal includes Nepal Medical College, Kathmandu University School of Medical Science, M.B. kedia Dental College and Lumbini Medical College. Out of 200 sample, 74 were right and 126 were left Humerus of human body. In 143 bone (i.e. 71.5%) a single nutrient foramen is present, in 44 bone (i.e. 22.0%) double nutrient foramen is present and triple nutrient foramen was also observed in 9 bone (i.e. 4.5%)whereas in 4 bone (i.e. 2.0%) no nutrient foramen were noticied. It was also noticed that nutrient foramen in 173, 15 and 3 bones were observed at medial, lateral and posterior border respectively. According to the foraminal index 1(0.5%) bone comes under Zone I, 182(91%) in zone II and zone III consists of 13(6.5%) bone and average foramina index of bone is calculated as 56.18 and the average length of Humerus is calculated as 27cm. Pearson correlation is significant at the 0.05 level which is significant for bone having single, double and triple nutrient foramen. In the study the nutrient foramen of 98.47% (193) Humerus directed downward toward the distal end of bone whereas in 1.53% (3) of bone nutrient foramen is directed vertically downward and no nutrient foramen is directed upward toward the proximal end. Conclusions Most of the nutrient foramen of humerus follows as per rule where as some of the bone with no nutrient foramen were founded and our result support the former researchers too.